Aluminum bioaccumulation and tolerance in Plantago algarbiensis Samp. and Plantago almogravensis Franco, assessed by using in vitro cultures and micropropagated plants - Martins, Neusa (2015)
This thesis aims to understand the aluminum (Al) bioaccumulation capacity, toxicity effects and tolerance mechanisms in two rare species endemic from Portugal, Plantago algarbiensis Samp. and Plantago almogravensis Franco. Firstly, two protocols were developed to propagate in vitro these species (Chapter 2). Afterwards it was investigated the influence of low pH on in vitro growth (Chapter 3). The seed germination requirements and the effects of Al on the germination and early development of seedlings were then evaluated in Chapters 4 and 5, respectively. The impact of low pH and Al on physiological responses, oxidative stress status and capacity for Al accumulation in micropropagated shoots and plantlets was investigated in the subsequent chapters (Chapters 6, 7 and 8). Finally, in Chapter 9 the possible implications of organic acids in Al detoxification were evaluated. Both species were successfully micropropagated showing high shoot multiplication rates and rooting frequencies and the micropropagated shoots of both species were able to tolerate and grow in low pH conditions. The seeds of both species germinate readily at 15 ºC and Al showed no impact on the germination percentage in either species but oxidative stress during early seedling development was detected. Although, both species accumulated considerable Al amounts and showed to be moderately tolerant to low pH and Al, P. almogravensis appeared to be more able to manage the oxidative stress and, therefore, adapted to maintain cellular physiology and growth under these stress conditions. Results suggested that Al detoxification in P. almogravensis implies both secretion of organic acids from roots and Al intracellular chelation by organic acids, while in P. algarbiensis only the internal mechanism seems to be involved. This research contributes to the understanding of the mechanisms underlying P. algarbiensis and P. almogravensis adaptation to acidic Al-rich conditions.